Edukasi Pola Hidup Bersih dan Sehat Pada Siswa SD Negeri Pabean Sebagai Upaya Mewujudkan Zero Waste - Yeriko Felis; Haniifatul Habiibah; Anastasia Wahyu Karno; Dita Megasari; Zainal Abidin Achmad (Universitas 45 Surabaya, 2024)
A Clean and Healthy Lifestyle (PHBS) is an activity that involves aspects of life to support physical and mental health. Implementing PHBS in schools plays an important role in creating a clean school environment. Educational activities at the Pabean Elementary School, Dringu District, Probolinggo Regency were carried out in 3 methods, namely the preparation, implementation and questionnaire stages. The results were obtained in the form of socialization in class 5A of SD Negeri Pabean regarding the application of PHBS in daily life and at school as well as a questionnaire in the form of student understanding before and after providing education. The student understanding rate before providing education was 66%, while student understanding after providing education was 83%. It is hoped that students' understanding can be applied in everyday life to create zero waste and a clean and healthy life.